Financing infrastructure at multilateral development banks: global administrative law and accountability reforms in infrastructure project financing in the BRICS bloc - Caswell, Grant Sinclair (Department of Public Law, 2022)
One of the hallmarks of the last decade has undoubtedly been the rise to prominence of a group of five emerging economies – Brazil, Russia, India, China and South Africa - that have come to be known collectively as the ‘BRICS bloc'. As a direct result of the increasingly prominent role of the BRICS bloc in global politics and economics, there has been a consequent increasing demand for improved infrastructure within these rapidly industrialising powers. This has compelled multilateral development banks to develop innovative funding solutions. Among these mechanisms is project finance, a relatively novel legal and financial structure typically used to fund public and private capital-intensive facilities and utilities. Multilateral development banks' (MDBs) participation in large-scale public-sector infrastructure projects financing is primarily governed by the loan agreements they conclude with governments, other financial institutions, and private sector entities. However, projects of this nature have predictably widespread effects, particularly on stakeholders not party to the contractual scheme – they frequently involve resettlement of local populations, transformation of indigenous lands, deforestation, pollution, and employment of labour for heavy industrial tasks. This far-reaching impact has necessitated increased accountability for MDBs' financing practices, particularly where the actions of MBD lenders impact on human rights and have broader social and environmental effects. This thesis examines two mechanisms to achieve accountability. The first of these solutions lifts the veil and entails reconceptualisation of how MDBs are held accountable at domestic level by reconfiguring the role of domestic judicial forums. The second is the formation of what is termed an independent ‘super mechanism', an international body which would be created by agreement among all participating multilateral development banks and would serve to provide effective oversight and enhanced accountability. This thesis ultimately focuses on advancing a novel contribution on the establishment of a super mechanism and it does so with reference to the interface between global administrative law principles and domestic administrative law principles. It addresses how supranational regulatory mechanisms should render the exercise of discretion and authority at the international level more transparent and accountable for the benefit of stakeholders in the developing world. The thesis formulates four benchmark criteria against which the development of an effective and successful super mechanism should be measured, it should: (i) be empowered with jurisdiction to conduct comprehensive investigations; (ii) provide remedies that are effective; (iii) be empowered to monitor and enforce remedies and corrective measures at MDBs; and (iv) operate in a manner that does not directly or indirectly contribute to undermining the national sovereignty of developing states. The thesis takes this further by examining how a super mechanism aligns with the core objectives and values of the BRICS bloc, and then advances a proposal to establish a BRICS super mechanism. It does this with reference to the practical challenges that may arise around the implementation of a BRICS-specific super mechanism, and it interrogates measures that the bloc has already implemented that may mitigate some of the theorised challenges.